TAX PAYMENT USING E-FILLING ON COMPANY IN PERUM GREEN VIEW CITY BATAM: AN INTRODUCTION - Tipa, Handra; Fajrah, Nofriani; Satria, Robby; Fauzi, Rahmat; Arista, Anggia; Elisa, Erlin (ASOSIASI IDEBAHASA KEPRI, 2024)
The General Directorate of Tax Regulations No. 47/PJ/2008 Article 1 Paragraph 7 states that e-Filing is an electronic method of filing SPT and the Annual SPT Extension Notification through the Application Service Provider. This process can be completed online and in real time. By utilizing the elffiling app, taxpayers may pay their taxes more easily. People with hectic schedules can especially benefit from this app, since it allows them to report their taxes without having to physically visit the tax office. People's faith in the tax system is increased since they can see and understand how tax dollars are spent more clearly. Sensitization and education regarding e-filing and the significance of tax payments are still required on a constant basis, even with a rise in awareness. It ensures that society may take full advantage of technological advancements and remains informed about changes in tax laws. It's critical to keep in mind that these conclusions are broad and flexible enough to be tailored to particular results in the dedicating process.